Development of Electronic Student Worksheets Integrated Guided Inquiry of Science Literacy to Increase Literacy HOTS in Reaction Rate Topic - Azzahra, Shafiah; Suyanti, Retno Dwi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This research aims to develop an Electronic Student Worksheets (E-LKPD) based on Guided Inquiry integrated with science literacy on reaction rate materials and analyze its feasibility, practicality, and effectiveness in improving students' science literacy HOTS. The method used is Research and Development (R&D) with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The research involved 3 material experts, 3 media experts, and 34 students of class XI MIPA MAN 1 Medan. The results of the development show that the E-LKPD Guided Inquiry Integrated Science Literacy media developed was declared very feasible based on the results of the average percentage of material experts of 89.29%, media experts of 87.50% with very high eligibility criteria. From the practical aspect, the media developed received a positive response from students with an average percentage of 91.8%, so it is classified as very practical. The effectiveness of the media is shown through the results of the n-gain calculation of 78% which is in the effective category, and strengthened by the results of the one sample t-test which shows a significant increase in the HOTS of students' science literacy. The percentage of achievement of the HOTS Literacy indicator shows that the analysis aspect (C4) obtained 77.15%, the synthesis (C5) of 79.51%, and the evaluation (C6) of 38.24%. Thus, it can be concluded that the E-LKPD media of Integrated Guided Inquiry of Science Literacy has the potential to increase students' HOTS Literacy on Reaction Rate Materials, especially in analytical and synthesis skills. The uniqueness of this research lies in the systematic integration between the syntax of guided inquiry and the science literacy component in interactive digital media to facilitate students' high-level thinking skills on the topic of reaction rate.